ANTIMICROBIAL ACTIVITIES FOR HADHRAMI HONEY ON GROWTH OF SOME PATHOGENIC BACTERIA - Al-Haddad, Ahmed M.; Al-Haik, Wedad M.; Al-kaf, Ali Gamal; Edrees, Wadhah Hassan (Universal Journal of Pharmaceutical Research, 2017)
Objectives: The majority of the Yemeni honey varieties are characterized by low moisture content, in addition to the various flora of Yemeni plant, which may not be found in many countries, which makes them of high medicinal importance and high monetary value. Methods: This study was carried out the effect of three types of Hadhrami honey: Somur, Sidr (Baghya) and Meria against the growth of some pathogenic bacteria (Pseudomonas aeruginosa, Proteus vulgaris, Escherichia coli, Enterobacter sp., Staphylococcus aureus, and Klebsiella sp.). Results: The results revealed that that Sidr honey gave the highest antibacterial activity against all bacteria tested, whereas the Somur and Meria honey were not recorded activity for growth Klebsiella sp. and Meria honey was not recorded activity for growth E. coli, respectively. When the antibiotics compared to types of honey antimicrobial activity, it was observed that the antimicrobial effect of Sidr honey was better than Imipenem antibiotic effect against P. aeruginosa. Conclusion: Study concludes that inhibition of the studied strains was dependent on the type of honey source. It is concluded that Yemeni honey could potentially be used as therapeutic agents against bacterial infection particularly to the tested microorganisms. Peer Review History: Received 9 October 2017; Revised 11 November; Accepted 30 December, Available online 15 January 2018 Academic Editor: Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com Reviewer(s) detail: Dr. Mujde Eryilmaz , Ankara University,Turkey, meryilmaz@ankara.edu.tr Omnia Momtaz Al-Fakharany , Tanta, University, Eygpt, amina.elfakharany@pharm.tanta.edu.eg